Occupational Safety Practices In Industries Of Nepal-Review (Journal of Namibian Studies : History Politics Culture, 2023)
Occupational safety and health promotion play a pivotal role in safeguarding the physical, mental, and social well-being of workers in diverse occupations. Unfortunately, the manufacturing industries in Nepal grapple with significant challenges pertaining to occupational safety. These challenges manifest in various forms, such as lack of sufficient safety equipment and training, unfavourable working conditions, precarious machinery and equipment, exposure to harmful chemicals, and inadequate fire safety measures. Consequently, this paper sets out to meticulously examine the occupational safety practices within Nepalese industries, focusing on safety measures, safety awareness, injury trends spanning a decade, and a comparative analysis with other nations. Through an extensive review of scholarly articles and research papers, a disquieting reality emerges – occupational safety practices in Nepal's industries have become an increasingly pressing concern, triggered by a surge in workplace accidents and illnesses. When compared with the practices of other countries, it becomes evident that Nepal lags behind many developed nations in the implementation of comprehensive safety measures and regulations within work environments. Indeed, Nepal's manufacturing industries face a multitude of occupational safety challenges, encompassing inadequate safety equipment and training, subpar working conditions, hazardous machinery, chemical exposure, and a lack of fire safety measures. Insights gleaned from various studies, focusing on safety measures, safety awareness, injury trends, and international comparisons, underscore the urgent need to address the escalating number of workplace accidents and illnesses. In conclusion, this study underscores the critical nature of occupational safety challenges confronting Nepal's manufacturing industries, emphasizing the imperatives of rectifying inadequacies in safety equipment, training, working conditions, machinery safety, chemical handling, and fire prevention measures.